2018
DOI: 10.1155/2018/4605769
|View full text |Cite
|
Sign up to set email alerts
|

Hybridized Symbiotic Organism Search Algorithm for the Optimal Operation of Directional Overcurrent Relays

Abstract: This paper presents the solution of directional overcurrent relay (DOCR) problems using Simulated Annealing based Symbiotic Organism Search (SASOS). The objective function of the problem is to minimize the sum of the operating times of all primary relays. The DOCR problem is nonlinear and highly constrained with two types of decision variables, namely, the time dial settings (TDS) and plug setting (PS). In this paper, three models of the problem are considered, the IEEE 3-bus, 4-bus, and 6-bus, respectively. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…Biogeography-based optimization (BBO) along with a new hybrid BBO with linear programming (BBO-LP) was used in [14]. Furthermore, Jaya algorithm [15], seeker optimization algorithm (SOA), simulated annealing-based symbiotic organism search (SASOS), and improved group search optimization (IGSO) were used in [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Biogeography-based optimization (BBO) along with a new hybrid BBO with linear programming (BBO-LP) was used in [14]. Furthermore, Jaya algorithm [15], seeker optimization algorithm (SOA), simulated annealing-based symbiotic organism search (SASOS), and improved group search optimization (IGSO) were used in [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In [29], the CFA was proposed to assess the coordination issues. In [30], a hybrid symbiotic organism optimizer was proposed to resolve OCR issue. In [31], comparative study was done using di erent metaheuristic algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [26] suggests that the coordination of the overcurrent relay is formulated as a nonlinear program by employing a group search optimization algorithm. In the paper by [27], the hybridized symbiotic organism search method is used to deal with the directional overcurrent relay problem. The authors found the optimal coordination of directional overcurrent relays by using a firefly algorithm [28].…”
Section: Introductionmentioning
confidence: 99%